BEHAVIORAL REGULATION IN SPORT QUESTIONNAIRE (BRSQ): USE IN YOUNG BRAZILIAN ATHLETES - Guedes,Dartagnan Pinto (2019)
ABSTRACT Introduction: The Behavioral Regulation in Sport Questionnaire (BRSQ) was originally proposed in English in order to identify sports motivation regulations according to the self-determination theory. Objectives: To translate into Portuguese, to perform cross-cultural adaptation, and to examine the psychometric properties of the BRSQ in a sample of young Brazilian athletes. Methods: The original version was translated according to international recommendations. A panel of judges analyzed the translated versions of the questionnaire, using semantic, idiomatic, cultural and conceptual equivalence as analysis criteria. The final version of the translated questionnaire was administered in a sample of 1217 young athletes (410 girls and 807 boys) aged 12 to 17 years. An exploratory factor analysis was carried out to identify initial psychometric properties, followed by a confirmatory factor analysis. Cronbach's alpha coefficient was used to assess the internal consistency of each factor associated with the BRSQ. Results: After minor changes identified in the translation process, the panel of judges was of the opinion that the Portuguese version of the BRSQ had semantic, idiomatic, cultural and conceptual equivalence. The factor analysis confirmed the structure of the eight factors proposed originally, through the statistical indicators χ2/gl = 1.87, CFI = 0.940, GFI = 0.945, AGFI = 0.958 and RMSR = 0.052 (95% CI 0.043 – 0.062). The Cronbach's alpha ranged from 0.71 to 0.85. Conclusions: Translation, cross-cultural adaptation and analysis of the psychometric qualities of the BRSQ were satisfactory, facilitating its application in future studies involving young athletes in Brazil. Level of Evidence III; Retrospective comparative study.